Comparative lipidomics analysis of HIV‐1 particles and their producer cell membrane in different cell lines. (10th January 2013) - Lorizate, Maier; Sachsenheimer, Timo; Glass, Bärbel; Habermann, Anja; Gerl, Mathias J.; Kräusslich, Hans‐Georg; Brügger, Britta
Summary Human immunodeficiency virus type 1 (HIV‐1) is a retrovirus that obtains its lipid envelope by budding through the plasma membrane of infected host cells. Various studies indicated that the HIV‐1 membrane differs from the producer cell plasma membrane suggesting virus budding from pre‐existing subdomains or virus‐mediated induction of a specialized budding membrane. To perform a comparative lipidomics analysis by quantitative mass spectrometry, we first evaluated two independent methods to isolate the cellular plasma membrane. Subsequent lipid analysis of plasma membranes and HIV‐1 purified from two different cell lines revealed a significantly different lipid composition of the viral membrane compared with the host cell plasma membrane, independent of the cell type investigated. Virus particles were significantly enriched in phosphatidylserine, sphingomyelin, hexosylceramide and saturated phosphatidylcholine species when compared with the host cell plasma membrane of the producer cells; they showed reduced levels of unsaturated phosphatidylcholine species, phosphatidylethanolamine and phosphatidylinositol. Cell type‐specific differences in the lipid composition of HIV‐1 and donor plasmamembranes were observed for plasmalogen–phosphatidylethanolamine and phosphatidylglycerol, which were strongly enriched only in HIV‐1 derived from MT‐4 cells. MT‐4 cell‐derived HIV‐1 also contained dihydrosphingomyelin as reported previously, but this lipid class was also enriched in the host cell membrane. Taken together, these data strongly support the hypothesis that HIV‐1 selects a specific lipid environment for its morphogenesis.